Response mechanisms of Polygonatum kingianum to temperature stress: implications for cultivation practices - Qian, Huali; Tao, Hong; Xu, Zhe; Chen, Xiaolei; Zhang, Lei; Dong, Jiahong; Ji, Pengzhang (Frontiers in Plant Science, 2025)
Polygonatum kingianum, a medicinally significant herb indigenous to Yunnan, China, exhibits pronounced sensitivity to temperature affecting its bioactive compound accumulation and growth. However, the molecular mechanisms underlying its response to temperature stress remain poorly characterized. To elucidate these mechanisms, we integrated physiological assessments with RNA-seq analysis of P. kingianum under controlled temperatures (10°C, 25°C, 30°C, and 35°C). The results indicate that P. kingianum exhibits optimal root growth at 10–25°C but shows poor adaptation to high temperature. Temperature stress led to inhibited root growth, accompanied by decreased chlorophyll content and leaf yellowing. This stress manifested as increased levels of malondialdehyde (MDA) and hydrogen peroxide (H2O2) in the leaves, along with elevated proline accumulation. In response to oxidative damage, the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), as well as the levels of non-enzymatic antioxidants (ascorbate/ASA and glutathione/GSH), were significantly upregulated. Transcriptome analysis further revealed that these physiological changes are regulated by multiple stress-related pathways, mainly including phenylpropanoid biosynthesis, glycolysis/gluconeogenesis, starch and sucrose metabolism, and plant hormone signaling. Additionally, 19 key genes encoding reactive oxygen species scavenging enzymes were identified and functionally characterized as core regulators of thermotolerance. This study deciphers the physiological and molecular mechanisms of the temperature stress response in P. kingianum.